Six new species of the genus Chevalia Walker, 1904 (Amphipoda, Corophiidea, Chevaliidae) from Brazilian waters, with a key to world species of the genus - Souza-Filho, Jesser F.; T. Souza, Ana Maria; Valério-Berardo, Maria Teresa (Zootaxa, 2010)
Six new species of the genus Chevalia are described from the Brazilian coast using all morphological characters proposed by Barnard & Thomas (1987) and Lazo-Wazen (1999) with two more: the shape of head proximal margin of lateral cephalic lobe and length ratio of uropod 2 rami: C. anomala sp. nov.; C. caetes sp. nov.; C. convexa sp. nov.; C. marajoara sp. nov.; C. thomasi sp. nov.; and C. setosa sp. nov. This paper raises the total number of recognized world species in this genus to 13. The genus is herein subdivided into three groups, based only on the shape of the basis of pereopod 7: group I – rectangular basis of pereopod 7 with a protuberant posteroventral corner, comprises four species; group II – rectangular basis of pereopod 7 lacking a protuberant posteroventral corner, comprises three species; and group III – ovate basis of pereopod 7, comprises seven species. A key of the world Chevalia species is also provided.